Development of an acoustic disruption (speech jammer) system using an electrostatic ultrasonic transducer array - Sunilkumar Akshay (Nanyang Technological University, 2023)
This project focuses on the development of a ‘Speech Jammer’ system that can be used to hinder the speech of any speaker. This project reports includes extensive research into the area of acoustic disruption devices, the plan, timeline, and the results of various tests done in order to produce a working Speech Jammer device that employs electrostatic ultrasonic transducers to carry the disrupting acoustic signal. The report includes numerous challenges encountered in the process of developing a working prototype for the proposed Speech Jammer device.